Public Participation in the Political Decision-Making Process in North Halmahera: A Village-Level Case Study of MKCM - Julando Tamudiman (Journal of Public Policy, Governance and Local Government, 2026)
Public participation is a central element of democratic village governance because it allows citizens to influence priorities, policy choices, and development decisions that directly affect their communities. This study examines the forms and level of public participation in the political decision-making process in MKCM Village, North Halmahera Regency, North Maluku Province, as well as the factors shaping participation and its implications for policy legitimacy and effectiveness. A qualitative case study approach was used. Data were collected through in-depth interviews, participant observation, and documentation involving village officials, members of the Village Consultative Body, community and religious leaders, women representatives, and residents involved in village deliberations. Data were analyzed interactively through data condensation, data display, and conclusion drawing. The findings show that participation is relatively active but remains predominantly representative through neighborhood heads, hamlet heads, and community leaders. Participation is visible in hamlet deliberations, village development planning forums, and the submission of community aspirations. Its quality is influenced by access to information, political awareness, communication, trust, and the responsiveness of the village government. Although participatory forums strengthen formal legitimacy and public acceptance of village decisions, substantive participation remains constrained by limited direct involvement, weak follow-up on community proposals, and continued domination by village elites. Strengthening transparency, feedback mechanisms, civic capacity, and inclusive deliberative spaces is therefore essential to improve democratic and responsive village decision-making.